PENDEKATAN DELONE AND MCLEAN UNTUK MENGKAJI EFEKTIVITAS SISTEM INFORMASI MANAJEMEN PAKET APLIKASI SEKOLAH (SIM-PAS) - Siti Marlina (LPPM Universitas Bina Sarana Informatika, 2017)
Technology development information is very fast, it has been changed by the process administration government offices education, as an evidenced by the use of information system package management application administration school in the process .The important things for using of information system package management application school is that this system can work out successful in use, One of indicators for successfull use the information system package management application school had been done effectively, by examined a neccesary variables, because whatever can be influenced by detect the effectiveness, extent of signification causal relationships between variables and influence diversity sex, education, age, and long use to benefit model the effectiveness of information system package management application school. This research adopt the successfull with delone and mclean model . Model delone and mclean have six variables that to success information system, consist of (1) the quality of information, (2) the quality of system, (3) the quality of services, (4) satisfaction users, (5) intent the use of, and (6) the net benefits. For Sample are taken by using quetionaire hosted by 210 respondents. Data processing uses the structural equation model ( SEM ) with the software AMOS v.20. The results of the study, it can be explianed causal relationships between quality information ( KI ) and quality of services ( KPL) with the use of (P) it is insignificant, the quality of information ( KI ) and quality of services ( KPL ) with satisfaction using (KP) center is also insignificant .The relationship between quality system and quality of services of User amount 47.8 % , the quality of system to satisfaction users of 56.2 % , the direct effect of the use of and satisfaction users to clean benefits of 47.8 %.